INVESTIGATING ZAKAT PAYMENT OF THAI MUSLIMS - Sawarai Boonyamanond; Papusson Chaiwat (Bank Indonesia, 2020)
This study examines Zakat payment among Thai Muslims whose wealth exceeds the minimum threshold (Nisab), thus are obliged to pay Zakat. It attempts to assess whether the amount of Zakat paid fulfils the requirement and to determine the amount of Zakat overpaid or underpaid, based on 2.5% of zakatable wealth, as measured by income from different sources. Using 460 questionnaires collected from Thai Muslims aged 15 years old and over who pay Zakat in 2015, this study employs a two-part model, in which the first part analyses the probability of fulfilling or not fulfilling an obligation to fully pay Zakat using the Multinomial Logit method of estimation, while the second part deals with the amount of Zakat overpaid/underpaid by using the Ordinary Least Square. It is found that the probability of fulfilling the required Zakat will increase and the amount of Zakat underpaid will decrease, if a person pays Zakat more than once a year, or the value of net assets of a person increases. In addition, for those whose Zakat payment is already higher than the amount required, trust and accountability of intermediate institutions or individuals who manage Zakat will positively affect the amount of Zakat overpaid considerably. Therefore, official organisations responsible for collecting, and distributing Zakat at the community, provincial, regional as well as national levels should be established with integrity, transparency, and good governance so that people would be encouraged to pay more Zakat and the lives of those in need can be lifted accordingly.